Enhancing free-space optical communication networks using Generalized Low Density Parity Check codes - Youssef, Albashir A.; Elsanadily, Sherif I. (Optics and laser technology, 2025)
Free Space Optical (FSO) communications gained impressive adoption in the research society. The high data rate, unlicensed frequency bandwidth, low cost, and immense security of FSO systems influence this much attention. Due to these benefits, FSO can fit into various communication system applications. Atmospheric turbulence (AT) is the main channel impairment faced by the FSO links, which affects their efficiency. Atmospheric turbulence existed due to haphazard variations of the air refractive index within communication duration. Several mathematical models are used to characterize the AT. The Log-Normal (LN) model exhibits weak and moderate turbulence, while for strong turbulence, the Gamma–Gamma (G-G) model is employed. The effects of geometric losses, weather attenuation, and misalignment errors are accounted for by maintaining the later models. So, the best candidate solution for enhancing FSO communication link performance is channel coding algorithms like Generalized Low-Density Parity Check (GLDPC) codes. This paper proposes a new FSO system that utilizes two novel GLDPC decoders to enhance the performance of the FSO communication channels and reduce its impairments. To demonstrate the effect of the proposed system on preserving cutting-edge GLDPC coding algorithms, all factors influencing FSO communications are also assessed. To evaluate the bit error rate (BER) of the proposed system combined with novel GLDPC decoders, the number of consumed iterations, dissipated decoding time, extracted throughput, and convergence of decoders are maintained. The findings demonstrated that, in the case of FSO communication channels, the new GLDPC decoding algorithms in the proposed system performed better than the current ones across all comparison points used in this investigation.